Consumo de cannabis en los estudiantes de secundaria de Barcelona: inicio en el consumo, efectos experimentados y expectativas Cannabis consumption among secondary school pupils of Barcelona [Spain]: initial use, reported effects and expectancies - Eva Morales; Carles Ariza; Manel Nebot; Anna Pérez; Francesca Sánchez (Gaceta Sanitaria, 2008)
Objetivos: Describir las circunstancias del inicio del consumo, las razones para hacerlo, los efectos experimentados y las expectativas relacionadas con el consumo de cannabis en adolescentes de Barcelona. Métodos: Encuesta transversal realizada a una muestra de escolares de 3.º de ESO en 2005. El cuestionario era confidencial y autocumplimentado. Se dispone de datos de 2.043 alumnos de 47 centros escolares de Barcelona. Resultados: El 37,5% de los escolares declaró haber probado el cannabis, de los cuales un 10% lo hizo en el último mes. El consumo fue superior en centros públicos que en concertados-privados (p < 0,001). El 60,3% probó el cannabis en el parque o en la calle. El 88,4% lo obtuvo de un compañero o amigo, y el 92,3% lo consiguió sin pagar. La principal razón para iniciar el consumo fue la curiosidad, y para continuarlo sentirse mejor y olvidar problemas. Los efectos experimentados más frecuentes fueron pérdida de memoria, tristeza y dificultades para estudiar o trabajar. El consumo de cannabis se relacionó positivamente con las expectativas de que relaja y facilita las relaciones sociales y sexuales, y negativamente con las creencias de que puede producir alteraciones intelectuales y del comportamiento, y tener efectos negativos para la salud. Conclusiones: El cannabis fue muy accesible: 9 de cada 10 escolares lo obtuvo de un compañero o amigo y sin pagar. Dos de cada 3 adolescentes reconocieron presentar efectos negativos debidos a su consumo. El conocimiento de las expectativas podría ayudar a explicar y prevenir el consumo de cannabis en adolescentes. Objectives: To describe the circumstances of initial use of Cannabis, as well as the reasons for consumption, reported effects and expectations related to cannabis use, among adolescents in Barcelona. Methods: A cross-sectional survey was conducted in a sample of pupils in the third year of compulsory secondary education in 2005. The questionnaire was confidential and self-completed. Data were gathered from 2,043 secondary school pupils from 47 schools in Barcelona. Results: A total of 37.5% of students reported cannabis consumption at some time, and 10.0% of these students had used cannabis in the previous month. Cannabis use was more common in public schools than in subsidized or private schools (p < 0.001). More than half the adolescents (60.3%) smoked cannabis for the first time in parks or on the street. Most (88.4%) of the adolescents obtained cannabis from a classmate or friend and 92.3% did so without paying for it. The main reason for initial consumption was curiosity, and reasons for continuing use were a desire to feel better and to forget problems. The most frequently reported effects were memory loss, sadness and difficulties in studying or working. Cannabis use was positively related to the expectation that the drug induces relaxation and aids social and sexual relations, and negatively to the beliefs that the drug can impair intellect and behavior and has negative effects on health. Conclusions: Cannabis was easily accessible to secondary school pupils and 9 out of 10 obtained the drug from a classmate or friend without paying for it. Two out of 3 adolescents reported negative effects as a consequence of cannabis use. Knowledge of expectations could help to explain and prevent cannabis consumption during adolescence.